En kvalitativ studie av studenters egenopplevde kompetanseutvikling gjennom videreutdanning : A qualitative study of students’ self-assessed competence development through further specialization as a nurse - Høyum, Gro Merethe; Olsen, Brita Fosser; Wevling, Astrid; Leonardsen, Ann-Chatrin Linqvist (Nordisk Tidsskrift for Helseforskning, 2022)
Healthcare services are getting more specialized, and this put high demands upon healthcare personnels’ competence. Studies indicate positive effects of further education for nurses. Few studies have examined the competence development process, or nurses’ perceptions about their new role as specialist nurses. This study aimed at exploring specialist nursing students’ self-reported competence development as well as whether this competence was appropriate for their new role as a specialist nurse. The study had a qualitative design, using semi-structured, in-depth interviews. Students perceived their new role as more challenging. The competence development felt demanding, and as a continuous process. The students felt that they had much more to learn. They experienced having startet on a path to knowledge-based practice, but that this still needed elaboration. Further nursing education provides competence as a foundation to fill a new role as a specialist nurse. Partaking further education is demanding, and it takes time before knowledge and skills are integrated as part of nurses’ professional practice.